2005
DOI: 10.1086/430878
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Molecular Hydrogen Emission in IC 63:FUSE, Hopkins Ultraviolet Telescope, and Rocket Observations

Abstract: We present far-ultraviolet observations of IC 63, an emission/reflection nebula illuminated by the B0.5 IV star Cas, located 1.3 pc from the nebula. Molecular hydrogen fluorescence was detected first in IC 63 by IUE and later at shorter wavelengths by ORFEUS. Here we present Far Ultraviolet Spectroscopic Explorer (FUSE ) observations toward three locations in the nebula, complemented by Hopkins Ultraviolet Telescope (HUT) data on the central nebular position. In addition, we present a sounding rocket calibrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 28 publications
6
33
0
Order By: Relevance
“…Models of UV pumping that incorporate X-ray irradiation and dust grain evolution (which regulates the penetration depth of FUV photons into the disk) show similar, high-v, low-J excitation diagrams (Nomura et al 2007). H 2 dissociation spectra in from these populations will be similar to the hot-star pumped H 2 fluorescence spectrum observed in photodissociation regions, where the continuum peak is clearly established at λ ≈ 1575 -1580Å (Witt et al 1989;France et al 2005), in contrast to the observed spectra in our CTTS survey. There may be other pathways to the formation of the highly non-thermal population distributions that give rise to the quasi-continuous and discrete emission lines observed in the CTTS sample, including the dissociation products of other molecular species and formationpumping of H 2 molecules newly formed on dust grains.…”
Section: Comparison With Infrared Spectrasupporting
confidence: 73%
“…Models of UV pumping that incorporate X-ray irradiation and dust grain evolution (which regulates the penetration depth of FUV photons into the disk) show similar, high-v, low-J excitation diagrams (Nomura et al 2007). H 2 dissociation spectra in from these populations will be similar to the hot-star pumped H 2 fluorescence spectrum observed in photodissociation regions, where the continuum peak is clearly established at λ ≈ 1575 -1580Å (Witt et al 1989;France et al 2005), in contrast to the observed spectra in our CTTS survey. There may be other pathways to the formation of the highly non-thermal population distributions that give rise to the quasi-continuous and discrete emission lines observed in the CTTS sample, including the dissociation products of other molecular species and formationpumping of H 2 molecules newly formed on dust grains.…”
Section: Comparison With Infrared Spectrasupporting
confidence: 73%
“…4 of France et al (2005), which means that the VUV-spectrum that interacts with the ice sample mimicks the molecular hydrogen photoexcitation Fig. 8.…”
Section: Astrophysical Implicationsmentioning
confidence: 92%
“…The nebula is illuminated by the star γ Cassiopeia located at projected distance d ⋆,sky = 1.3 pc from the star and the attenuated ISRF. Physical parameters adopted for IC 63, including gas density n(H2), temperature Tgas, dust temperature T d (Jansen et al 1994;Jansen et al 1996;France et al 2005) and the parameters of γ Cas are listed in Table 1. Based on the geometry of the diffuse emission, Andersson et al (2013) found that IC 63 and γ Cas are offset from each other along the sightline, with the line between γ Cas and IC 63 making an angle of γ⋆ = 58 • with respect to the plane of the sky (henceforth POS).…”
Section: Physical Model Of Ic 63 and Model Set Upmentioning
confidence: 99%